A Doutrina Cronos: O quarto padrão da política dos Estados Unidos para a China (2009-2018) - Rocha, Mateus de Paula Narciso (2020)
This study examines the structural power of the United States and the goals and perceptions of the governments of Barack Obama (2009-2017) and Donald Trump (2017 2018) in relation to China. Through the analysis of indicators, it was noted that the United States is the structural hegemony, but, after the turn of the century, the disparity of power vis-à-vis China has been reduced in the productive structure. Considering this change as the independent variable, the hypothesis is that the United States would be interested in a revisionist foreign policy, especially in the trade arena, to slow down China's economic strengthening. Next, to understand the US policy towards China and the validity of the hypothesis, we analyze the Executive’s actions and a series of documents: the presidential debates; the State of The Union Address; the National Security Strategy; the Quadrennial Defense Review; the Presidential Trade Policy Agenda; the Report to Congress on China's WTO Compliance and the Special 301 Report. Despite differences in method and sense of urgency, the continuity of strategic objectives for China was noted in the Obama and Trump governments. In both administrations, trade policy was used to counteract China’s industrial policies, as well the Pentagon, the White House, and the USTR perceived China as the great power that most threatens US interests. In addition, Obama and Trump conducted diplomatic campaigns to block Beijing’s relative gains, fostered the idea of China as an economic adversary in the domestic public, and deepened the “position-taking strategy” in Eurasia, specifically the “Andrew Marshall’s Agenda”. Thereby, China was perceived and treated as an economic and geopolitical adversary, and a revisionist policy to strangle China's economic strengthening took place. Thus, without being an exception to the historical rule, the White House sought to protect the economic arm of its power and to weaken the future trend in which another superpower emerges. Therefore, considering the historical trajectory, there was a “goal change” in the foreign policy of the United States, setting a new bipartisan pattern for China policy.